ANALISIS DAERAH BINTIK MANIS PADA PERANCANGAN RAKET BULUTANGKIS - Budiwantoro, Bagus; Suweca, I Wayan; Sibuea, Roby C. M (Mesin, 1998)
One method to increase badminton racket performance is by improving individual players racket. For this purpose, two measurements are necessary, i.e. (1) the racket âs location of sweet spot that is inherent due to its manufacturing process and (2) the players